Assessing employees perception on health and safety management in public hospitals - Chew Abdullah, Nor Azimah; Spickett, Jeffery T.; Rumchev, Krassi B.; Dhaliwal, Satvinder S. (2013)
This article examined the perception of employees regarding the management of Occupational Health and Safety (OHS) in public hospital in Malaysia.418 employees from three state hospitals in the northern region of Malaysia participated in this study and that gave a response rate of 43.15%. Data was collected using a set of questionnaires which consists of variables including safety satisfaction and feedback, safety communication, role of supervisor, work pressure, training and competence, management commitment, safety involvement, safety objectives, safety reporting, and leadership style.Data analysis was done using descriptive statistics, t-test, one-way ANOVA, Pearson correlation and multiple regressions.Findings showed that employees perceived safety reporting as the most important dimension and work pressure as the least important component in the OHS practices in their workplaces.Empirical evidence indicated that there was no significant difference in safety satisfaction and feedback between male and female workers but there was a significant difference among these employees in safety involvement.In addition, results also showed that there was a significant difference in safety satisfaction faced by job position like nurse but there was no significant difference between employees with job tenure comprise of less than 1 year, 2 to 15 years, and 16 years and above.Findings suggested that there was a significant positive correlation between safety satisfaction and feedback and safety communication, safety involvement, training and competence, safety reporting, work pressure, safety objectives, management commitment, role of supervisors, and leadership style.Regression analysis revealed approximately 54.5% (R2 = 0.545) of variance in safety satisfaction and feedback, that was simultaneously explained by five independent variables including safety involvement, safety reporting, work pressure, management commitment, and safety objectives.